2020
DOI: 10.1113/jp279705
|View full text |Cite
|
Sign up to set email alerts
|

Ketamine anaesthesia induces gain enhancement via recurrent excitation in granular input layers of the auditory cortex

Abstract: Ketamine is a common anaesthetic agent used in research and more recently as medication in treatment of depression. It has known effects on inhibition of interneurons and cortical stimulus-locked responses, but the underlying functional network mechanisms are still elusive. r Analysing population activity across all layers within the auditory cortex, we found that doses of this anaesthetic induce a stronger activation and stimulus-locked response to pure-tone stimuli. r This cortical response is driven by gain… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
41
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 66 publications
5
41
1
Order By: Relevance
“…Those short-latent sinks reflect the synaptic afferent input from the lemniscal auditory part of the thalamus, the ventral medial geniculate body (vMGB), with main projections to granular layers and collaterals within layer Vb [26][27][28] . This has been revealed by earlier studies showing persistent thalamocortical inputs in corresponding layers after intracortical silencing with the GABA A -agonist muscimol 22,23,29 in accordance with reports by others 28,30 . Early sinks were followed by synaptic activation of supragranular (I/II) and deep infragranular (VI) layers ( Fig.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Those short-latent sinks reflect the synaptic afferent input from the lemniscal auditory part of the thalamus, the ventral medial geniculate body (vMGB), with main projections to granular layers and collaterals within layer Vb [26][27][28] . This has been revealed by earlier studies showing persistent thalamocortical inputs in corresponding layers after intracortical silencing with the GABA A -agonist muscimol 22,23,29 in accordance with reports by others 28,30 . Early sinks were followed by synaptic activation of supragranular (I/II) and deep infragranular (VI) layers ( Fig.…”
Section: Resultssupporting
confidence: 92%
“…In this study, we investigated the effects of ECM removal acutely and under ketamine-xylazine anesthesia. We have recently shown that, in addition to generally very similar spatiotemporal activity patterns, anesthesia mainly influences gain enhancement in layer III/IV at best frequency stimulation 29 . Particularly, ketamine-xylazine had only minor effects on the spectral beta range and off-BF-evoked activity, which showed strongest effects after HYase treatment.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In this study, we investigated the effects of ECM removal acutely and under ketamine-xylazine anaestesia. We have recently shown that, in addition to generally very similar spatiotemporal activity patterns, anesthesia mainly influences gain enhancement in layer III/IV at best frequency stimulation (Deane et al, 2020). Particularly, ketamine-xylazine had only minor effects on the spectral beta range and off-BF-evoked activity, which showed strongest effects after HYase treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The location of the field AI in primary ACx was identified by vasculature landmarks and physiological parameters (Happel et al, 2010). In this study, we analyzed only data from recordings which exceed 90 minutes after implantation of the electrode–a state where the cortical responses under anesthesia have been largely stabilized as reported recently (Deane et al, 2020).…”
Section: Methodsmentioning
confidence: 99%